Pengembangan Model Pendeteksian Gambar Alat Musik dengan Metode Faster R-CNN dengan Library Keras - Ivan Septian; Henry Septanto (UNIVERSITAS KALBIS, 2022)
This research discusses developing a musical instrument image detection application with a frcnn library method. The purpose of this study is to detect types of musical instruments using the fastest R-CNN as a method of detecting objects. The problem with using RCNN is the length of time of computing. It takes about a minute to process the image data, so the training process will take a very long time. Therefore, researchers use the fastest r-cnn method to get the output quickly.